CONTINUING PROFESSIONAL DEVELOPMENT ACTIVITIES FOR ENGLISH TEACHERS - Nana Priajana (IAIN Syekh Nurjati Cirebon, 2017)
Abstract: Teachersâ€™ quality plays a paramount role in the improvement of quality of education. A way to ensure high quality teachers is through effective continuous professional development for teachers. This present study is aimed to explore how the EFL teachers develop their professionalism particularly in terms of pedagogical and professional competencies. The result shows that there are three main themes of professional development pursuits of EFL teachers comprising of self-initiated or individual, institutional, and non-institutional professional development activities.Â Â Keywords: continuing professional development, EFL teachers, pedagogical competency, professional (subject matter) competency